Diagnostic Value of Eye Opening in Infantile Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
The significance of eye opening and closure during paroxysmal events in infants was examined by a retrospective review of video electroencephalograms of 91 seizures recorded in 69 infants at the Epilepsy Center, Children's Memorial Hospital, Chicago, IL.